Stereocontrolled synthesis of Hagen's gland lactones via iterative proline catalyzed alpha-aminoxylation and oxa-Michael addition reactions - Kauloorkar, Shruti Vandana; Jha, Vishwajeet; Jogdand, Ganesh F.; Kumar, Pradeep (RSC Advances, 2015)
A simple and efficient synthesis of Hagen's gland lactones was achieved using a sequential alpha-aminoxylation/oxa-Michael approach in a highly diastereoselective manner with assignment of relative configurations. This method was found to be applicable to the synthesis of various other isomers of Hagen's gland lactones.